Epidemiology of cutaneous Leishmaniasis and taxonomy of phlebotomians sandflies in the Tafingoult village (Taroudant – Morocco) - Youssef, EL GHRIFI; BENCHAHID, Abdelfatah; Nouhaila, BELGHYTI; FRAINE, Charaf; ELBAKRI, Fatima Zahrae; TAIBA, Riam; ELALAOUI, Zakaria; HABIBY, El Moctar; ELKHARRIM, Khadija; BELGHYTI, Driss (Edelweiss Applied Science and Technology, 2024)
Leishmaniasis is endemic in 66 countries in Southern Europe, Africa, the Middle East and Asia and in 22 countries in North, South and Central America. In Morocco, leishmaniasis was first described by Remlinger in 1913 and became a concern in the 1970s. The main objective of our study is to carry out a taxonomic inventory of sandfly vectors and to screen for cases of human leishmaniasis in Tafingoult village (Taroudant, Southern Morocco). Our work will strengthen the development of an eco-epidemiological research program for the eradication of leishmaniasis in this region. This collaborative survey was carried out between the Tafingoult Health Center and the Faculty of Sciences of Kenitra. The diagnosis of leishmanian wounds by the scraping method was carried out by a sterile vaccinostyle in the infiltrated part far from the superinfected areas. The product of the scraping and the collection of serosities were used to make stained smears with Giemsa and examined under a microscope with a 100 objective under immersion oil. The method of capturing sandflies focused on the aerial volatile phase using adhesive traps in the form of 25 x 20 cm surface paper panels impregnated with castor oil. The traps are placed overnight in the resting places of the sandflies. The next morning, the captured insects are removed and placed in labeled tubes containing 70% alcohol. Species identification is performed using guides or determination keys established by Bailly-Choumara and collaborators, based on morphoanatomical and biometric criteria. The results of the epidemiological survey revealed 87 positive cases of cutaneous leishmaniasis due to Leishmania tropica which were classified: 1 case had three lesions, 9 cases had 2 lesions and the rest of the 77 cases had a single lesion. The captured sandflies were identified as belonging to the species Phlebotomus Sergenti and Phlebotomus longicuspis. Our study revealed the persistence of cutaneous leishmaniasis in the region and suggests strengthening the epidemic eradication services.